PENGARUH TEMPERATUR TEMPER TERHADAP SIFAT MEKANIK DAN KETAHANAN KOROSI PADUAN Fe-1,52Al-1,44C - Kartikasari, Ratna (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
On the basis of economic and lower density considerations, Fe-Al-C alloy could be a good candidate for replacing some of the conventional stainless steel. Wherein, Al is used to replace the expensive alloy element in conventional Fe-Cr-C system. The aim of the research is to investigate tempering temperature influence to mechanical properties and corrosion resistance of Fe-1,52Al-1,44C in the 3.5% NaCl solution. Fifty kilograms of Fe-Al-C were prepared from mild steel scrap, high purity aluminium, and Fe-C. The alloy was prepared in a high frequency induction furnace with alloying was done in the ladle. Optical microstructure, mechanical properties and corrosion rate were examined. The corrosion rate, were carried out with immersion methode in 3.5% NaCl. The optical micrograph shows that as cast Fe-1,52Al-1,44C alloy has ferrite and pearlite microstructure and has tendency to become ferritic microstructure with encreasing tempering temperature. Maximun tensile strength and maximum hardness took placed after hardening that was respectively 74,44kg/mm2 and 298,7 VHN. Maximum elongation was reached at 450oC tempering temperature. The result of corrosion testing showed that the alloy has decreasing corrosion rate with the increasing tempering temperature.